Acetylcholine Esterase Inhibitory Potential and Antioxidant Activity of Various Extracts of Leucas cephalotes and Juglans regia L. - Shahwar, Durre; Naz, Misbah; Asam Raza, Muhammad; Ara, Gulshan; Yasmeen, Asma; Saeed, Afifa; Bokhari, Sana; Ajaib, Muhammad; Ahmad, Naeem (Asian Journal of Chemistry, 2012)
The aerial parts of Leucas cephalotes were extracted in n-hexane, chloroform and ethyl acetate successively, while seeds of Juglans regia L. were extracted in n-hexane and ethyl acetate. Column chromatography of the n-hexane fraction of J. regia yielded eight fractions. Total phenolic contents were calculated using Folin-Ciocalteu (FC) reagents while, 2,2-diphenyl-1- picrylhydrazyl (DPPH) scavenging, ferric reducing antioxidant power (FRAP) and acetylcholine esterase (AChE) inhibition potential of all extracts/fraction was evaluated according to their respective in-vitro models. Ethyl acetate extract of L. cephalotes contained highest total phenols (864.5 ± 1.2 mg GAE/g of extract) with 83.3 ± 1.1 % DPPH activity and IC50 value 271 ± 6 μg/ mL. The column fractions of J. regia (JRH-8) demonstrated significant antiradical activity (80.8 ± 1.1 %, IC50 = 283 ± 4 μg/mL). All extracts/fractions showed remarkable FRAP activity. The n-hexane extracts of both plants exhibited maximum enzyme inhibition activity 78.7 ± 1.1 % (IC50 = 175 ± 4 μg) and 73.5 ± 1.5 % (IC50 = 108 ± 3 μg) for J. regia and L. cephalotes respectively.